Enhancing surgical planning of distal splenopancreatectomy through 3D printed models: a case report - Arsenkov, Stefan; Plavevski, Ognen; Nikolovski, Andrej; Arsenkov, Ljuben; Shurlani, Arben; Saliu, Valon (Oxford University Press (OUP), 2023)
Abstract The complex anatomy of the peripancreatic region was a challenge to many surgeons in the past. Up until recently, the only way to prepare and plan a surgery was through the use of traditional 2D images, obtained via computed tomography or magnetic resonance imaging. Recently, the advantages in the field of 3D printing (also called additive manufacturing, or rapid prototyping) allowed the creation of replicas of the patient’s anatomy which is to be used for preoperative planning and visual reference. We present the case of a 46-y.o. patient with a distal pancreatic lesion requiring a distal splenopancreatectomy, who benefited from the use of 3D printing technology. No intraoperative or postoperative complications were encountered, while the created model was used to plan and perform the needed resection.